A simplified approach for design of steel-GFRP hybrid reinforced concrete sections. (1st March 2023) - Ibrahim, Mostafa; Asadian, Alireza; Galal, Khaled
Highlights: Recommendations for the design of steel-GFRP hybrid RC flexural elements are proposed. Design charts for transforming steel RC sections to hybrid RC sections are developed. A procedure to obtain the replacement ratio of a hybrid RC section is proposed. The accuracy of the design charts is validated against over 37, 000 steel RC slabs. Abstract: The corrosion of steel reinforcement is one of the main reasons for the deterioration of reinforced concrete (RC) structures subjected to harsh environments. Glass fibre-reinforced polymer (GFRP) reinforcing bars have emerged as an ideal solution at an affordable cost for eliminating this issue. The design of steel RC elements can be controlled by ultimate limit state (ULS) requirements, resulting in over-designed sections for the serviceability limit state (SLS). On the other hand, the design of GFRP RC elements is typically controlled by SLS checks, resulting in over-designed sections for the ULS. Replacing some steel rebars with GFRP bars could be an economical solution in the case of a shortage in the supply of steel rebars, especially in large quantities of steel reinforcement. This replacement with GFRP bars would be even more economically attractive if the replaced steel bars were stainless, epoxy-coated, zinc-coated or galvanized. This research aims to set a platform for designing steel-GFRP hybrid RC sections. Based on fundamental theories of reinforced concrete beams and the available literature, design considerations are suggested for the design of steel-GFRP hybrid RC flexural elements. Using the proposed design recommendations, an analytical study was undertaken to develop simplified design charts for transforming steel RC sections to alternative steel-GFRP hybrid RC sections with the same total number of bars. This research proposes a step-by-step design procedure using design charts to find a replacement ratio of an alternative steel-GFRP hybrid RC section using properties of a steel GFRP RC section that would suit its design purpose.